Electron density and chemical bonding I : Experimental charge density studies - Stalke, Dietmar (Structure and Bonding, 2012)
D. Stalke, U. Flierler: More than Just Distances from Electron Density Studies.- A.O. Madsen: Modeling and Analysis of Hydrogen Atoms.- B.B. Iversen/J. Overgaard: Charge Density Methods in Hydrogen Bond Studies.- U. Flierler, D. Stalke: Some Main Group Chemical Perceptions in the Light of Experimental Charge Density Investigations.- D. Leusser: Electronic Structure and Chemical Properties of Lithium Organics Seen Through the Glasses of Charge Density.- L. J. Farrugia, P. Macchi: Bond Orders in Metal-Metal Interactions Through Electron Density Analysis.- W. Scherer, V. Herz, Ch. Hauf:  On the Nature of β-Agostic Interactions: A Comparison Between the Molecular Orbital and Charge Density Picture.